Efeito da desordem catiônica nas propriedades magnéticas da ferrita de zinco - Jesus, Camilo Bruno Ramos de (2012)
In this work, we have investigated the structural and magnetic properties of ZnFe2O4 samples prepared via solid state reaction and co-precipitation obtained for using different annealing temperatures. Measurements of X-ray diffraction (XRD) were realized in order to verify both the single phase was obtained, as well as to determine the purity of the sample with respect to the amount of spurious phase existent. The magnetic characterization was carried out through magnetization measurements as function of applied magnetic field (65 < H < 65 kOe) and as function of temperature (2 < T < 400 K) using a magnetometer SQUID of the Quantum Design MPMS SQUID-EverCool. Besides, we analyze the dependence of the coercive field with the temperature in ZnFe2O4 nanoparticles. A theoretical model that considers the distribution of particles sizes was used to make the adjustment to our experimental data of coercivity as function of temperature